FEMINISTIK TARJIMASHUNOSLIK NUQTAI NAZARIDAN AYOL ROMANLARINI TAHLIL QILISH (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article explores the analysis of women’s novels from the perspective of feminist translation studies, focusing on the interaction between gender, language, and culture in the translation process. Feminist translation theory emphasizes the role of the translator not only as a mediator of meaning but also as an active participant in reconstructing female identity and voice within the target language. The study examines how gender-specific linguistic features, cultural representations, and ideological elements are conveyed or transformed in translation. Particular attention is given to the strategies used to preserve or reinterpret women’s experiences, emotions, and social roles in literary texts. The research is based on a comparative analysis of selected English and Uzbek women’s novels and their translations.